CRISPR-based assay reveals SARS-CoV-2 RNA dynamic changes and redistribution patterns in non-human primate model. Issue 1 (31st December 2022) - Huang, Zhen; Zhang, Lili; Lyon, Christopher J.; Ning, Bo; Youngquist, Brady M.; Niu, Alex; Beddingfield, Brandon J.; Maness, Nicholas J.; Saba, Nakhle S.; Li, Chen-Zhong; Roy, Chad J.; Hu, Tony Y.
ABSTRACT: Mounting evidence indicates that SARS-CoV-2 can infect multiple systemic tissues, but few studies have evaluated SARS-CoV-2 RNA dynamics in multiple specimen types due to their reduced accessibility and diminished performance of RT-qPCR with non-respiratory specimens. Here, we employed an ultrasensitive CRISPR-RT–PCR assay to analyze longitudinal mucosal (nasal, buccal, pharyngeal, and rectal), plasma, and breath samples from SARS-CoV-2-infected non-human primates (NHPs) to detect dynamic changes in SARS-CoV-2 RNA level and distribution among these specimens. We observed that CRISPR-RT–PCR results consistently detected SARS-CoV-2 RNA in all sample types at most time points post-infection, and that SARS-CoV-2 infection dose and administration route did not markedly affect the CRISPR-RT–PCR signal detected in most specimen types. However, consistent RT-qPCR positive results were restricted to nasal, pharyngeal, and rectal swab samples, and tended to decrease earlier than CRISPR-RT–PCR results, reflecting lower assay sensitivity. SARS-CoV-2 RNA was detectable in both pulmonary and extrapulmonary specimens from early to late infection by CRISPR-RT–PCR, albeit with different abundance and kinetics, with SARS-CoV-2 RNA increases detected in plasma and rectal samples trailing those detected in upper respiratory tract samples. CRISPR-RT–PCR assays for SARS-CoV-2 RNA in non-respiratory specimens may thus permit direct diagnosis of suspected COVID-19 cases missed by RT–PCR, while tracking SARS-CoV-2 RNA in minimally invasive alternate specimens may better evaluate the progression and resolution of SARS-CoV-2 infections.